Influence of land use on soil quality and stratification ratios under agro-silvo-pastoral Mediterranean management systems (Agriculture, Ecosystems & Environment, 2014)
a b s t r a c t A case study from north-eastern Sardinia (Italy) in semiarid conditions is presented. Agriculture is mainly extensive and markedly agro-silvo-pastoral, and is typical of similar areas of the Mediterranean basin. The following land uses at different levels of crop intensification were considered: tilled vineyard (TV), no-tilled grassed vineyard (GV), hay crop and pasture with sparse cork oaks (HC and PA), semi-natural systems (SN, former vineyards set-aside about 30 years ago), cork oak forest (Quercus suber L.) established in the past century (CO). Some soil quality parameters were considered: soil organic carbon (SOC) and total N (TN) concentrations, stocks and their stratification ratios with depth (SRs), microbial biomass carbon (MBC) and its quotient to SOC (qmic), and C:N ratios. Both in terms of concentrations and stocks, SOC and TN were generally higher in HC, PA, CO and SN: in these land uses SOC in the topsoil were in the range 17.0–24.3 g kg−1 and 48.9–65.4 t ha−1; TN values were 1.07–2.08 g kg−1 and 3.1–6.0 t ha−1. SOC and TN SRs under the CO land use were higher than 4, quite above the proposed threshold (?2), >2 in GV, and ≥2.0 in PA. MBC in mg kg−1 and qmic in ?g g−1 were higher under CO (194 and 0.89) and GV (156 and 0.97). C:N ratios had optimum or nearly optimum (9–12) values in CO, PA and the GV, in agreement with the SRs, MBC and qmic. A positive and significant correlation was found between SOC and TN concentrations in all the land uses. ©

Changes in soil organic carbon and climate change – Application of the RothC model in agro-silvo-pastoral Mediterranean systems - Francaviglia, Rosa; Coleman, Kevin; Whitmore, Andrew P.; Doro, Luca; Urracci, Giulia; Rubino, Mariateresa; Ledda, Luigi (Agricultural Systems, 2012)
Due to the complexity of soil organic carbon (SOC), models have proved very useful in helping to improve our understanding of the soil–plant–atmosphere system. In this study we used the Rothamsted carbon model (RothC), which considers the effect of climate (temperature, rainfall and evaporation), soil texture (clay content) and crop management on the decomposition processes, to predict changes in SOC under different land uses and the different climate that may occur in the future. SOC turnover was evaluated in land uses under different levels of agricultural intensiﬁcation. The agriculture of the study-area is mainly extensive and markedly agro-silvo-pastoral, and is typical of northeastern Sardinia (Italy) and similar areas of the Mediterranean basin. The following land uses were considered: vineyards, hay crops, pastures, semi-natural systems (formerly vineyards) and cork oak forests. Since the study-area is characterized by the same soil type (Haplic Endoleptic Cambisols, Dystric) derived from granitic rocks and potential native vegetation (Quercus suber L.), this was considered as the model baseline to study soil organic carbon dynamics. Climate change scenarios for 90 yr were generated from the baseline climate with two Global Climate Models: GISS (Goddard Institute of Space Studies, USA), and HadCM3 (Met Ofﬁce, Hadley Centre, UK), for two of the Intergovernmental Panel on Climate Change (IPCC) emission scenarios (SRES A2 and B2). Land uses at low cropping intensity were more efﬁcient than intensive agricultural systems in terms of SOC storage in the order: hay crop > pasture > cork oak forest > semi-natural systems. Land use change to vineyards decreased the carbon balance signiﬁcantly between 0.09 and 0.15 t C ha 1 yr 1 . However, former vineyards have almost recovered from soil disturbance following the establishment of the vineyards.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: C sequestration; climate change; CO2 emissions; Emission scenarios; land use; RothC